An Unusual Case of Surma (Eye Cosmetic) Induced Conjunctival and Scleral Ulceration - Chandana Chakraborti; Nabanita Barua; Ajoy Kr Saha; Rupanjili Lakra (Delhi Journal of Ophthalmology)
Surma is traditionally applied to conjunctiva and eyelids for cosmetic purpose in many centuries. It contains preservatives and additives like lead, nickel, mercury that can lead to dry eye, blepharitis, allergic conjunctivitis, iritis and periocular dermatitis. We report a case of “surma” induced conjunctival & partial thickness scleral ulceration in a 60 years old female. She presented with sudden swelling and burning sensation in right eye after applying ‘surma’ in her right eye. Conjunctival and scleral ulceration was noted subsequently. She was treated conservatively with topical and oral steroid. This unusual complication of surma is not documented in literature.